Mucins and Tight Junctions are Severely Altered in Necrotizing Enterocolitis Neonates - Liu, Dong; Xu, Yanzhen; Feng, Jinxing; Yu, Jialin; Huang, Jinjie; Li, Zhiguang (American Journal of Perinatology, 2020)
Objective This study investigates the expression levels of mucin 1 (MUC1), MUC2, occludin, and zonula occludens-1 (ZO-1) in necrotizing enterocolitis (NEC).Study Design Intestinal specimens of surgical patients suffering from NEC (the NEC group) and intestinal specimens of patients with congenital intestinal atresia (the control group) were collected. Immunohistochemical changes in MUC1, MUC2, occludin, and ZO-1 were compared between the two groups.Results Our study showed a significant decrease in the expression levels of MUC1 (p = 0.004), MUC2 (p = 0.001), occludin (p = 0.004), and ZO-1 (p = 0.013) in neonates suffering from NEC as compared with the control group.Conclusion Mucins and tight junctions are severely altered in NEC neonates. This finding might provide clues for rupture of the intestinal barrier. Further research is needed to investigate the gene expression as well as the exact mechanisms behind these changes. This will help us better understand the role of the intestinal barrier in NEC.Key Points
Keywords: NEC; MUC1; MUC2; ZO-1; occluding; intestinal barrier